2015
DOI: 10.1530/rep-15-0178
|View full text |Cite
|
Sign up to set email alerts
|

An alkaline follicular fluid fraction induces capacitation and limited release of oviduct epithelium-bound stallion sperm

Abstract: Induction of hyperactivated motility is considered essential for triggering the release of oviduct-bound mammalian spermatozoa in preparation for fertilization. In this study, oviduct-bound stallion spermatozoa were exposed for 2 h to: i) pre-ovulatory and ii) post-ovulatory oviductal fluid; iii) 100% and iv) 10% follicular fluid (FF); v) cumulus cells, vi) mature equine oocytes, vii) capacitating and viii) non-capacitating medium. None of these triggered sperm release or hyperactivated motility. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 81 publications
3
29
0
2
Order By: Relevance
“…This would allow HCO 3 K and albumin exposed sperm to proceed immediately along the mare's oviduct to the site of fertilization without an obligatory period of epithelial binding. Nevertheless, sperm bound to oviduct epithelium should be able to react to capacitation triggers in the oviduct, such as elevated pH (Leemans et al , 2015, to achieve full fertilizing capability. Full and proper initiation of capacitation will presumably release sperm optimally primed to fertilize from the oviduct epithelium (Leemans et al 2015).…”
Section: Oviduct Binding Of Stallion Spermmentioning
confidence: 99%
“…This would allow HCO 3 K and albumin exposed sperm to proceed immediately along the mare's oviduct to the site of fertilization without an obligatory period of epithelial binding. Nevertheless, sperm bound to oviduct epithelium should be able to react to capacitation triggers in the oviduct, such as elevated pH (Leemans et al , 2015, to achieve full fertilizing capability. Full and proper initiation of capacitation will presumably release sperm optimally primed to fertilize from the oviduct epithelium (Leemans et al 2015).…”
Section: Oviduct Binding Of Stallion Spermmentioning
confidence: 99%
“…Anteriormente, se ha podido reconocer para otras especies que el fluido folicular favorece ciertas funciones asociadas con la capacidad fecundante como la movilidad y la reacción acrosomal (Yanagimachi, 1969;Tesarík, 1985;Suarez et al, 1986;Morales et al, 1989;Ravnik et al, 1990;Hansen et al, 1991;McNutt y Killian, 1991;Ravnik et al, 1992;McNutt et al, 1994;Cheng et al, 1998;Jeon et al, 2001;Thérien et al, 2001;Briton-Jones et al, 2001;Schuffner et al, 2002;Getpook y Wirotkarun, 2007;Esmaeilpour et al, 2014;Leemans et al, 2015). Estudios previos en nuestro laboratorio determinaron que el fluido folicular favorece la movilidad espermática en alpaca (Bravo y Valdivia, 2017).…”
Section: Discussionunclassified
“…Se ha podido observar que el fluido folicular puede estimular las funciones espermáticas relacionadas con la capacidad fecundante en varias especies. Por ejemplo, se ha reconocido que el fluido folicular tiene un efecto favorable en la movilidad espermática (Yanagimachi, 1969;Tesarík, 1985;McNutt et al, 1994;Jeon et al, 2001;Briton-Jones et al, 2001;Getpook y Wirotkarun, 2007;Esmaeilpour et al, 2014;Leemans et al, 2015) y la reacción acrosomal (Yanagimachi, 1969;Thérien et al, 2001;Thérien et al, 2005). En el caso de la alpaca, Bravo & Valdivia (2017) pudieron observar que el fluido folicular estimulaba la movilidad espermática.…”
Section: Introductcionunclassified
“…Recently, we demonstrated that, of a range of potential physiological triggers, only heat-inactivated, charcoal-treated, 30 kDa filtered or triple treated follicular fluid (pH 7.9) was able to induce hyperactivated motility and release of stallion spermatozoa bound to oviduct explants. However, while a significant proportion of bound spermatozoa showed hyperactivated motility combined with tail-associated protein tyrosine phosphorylation, only a small number of spermatozoa detached from the oviduct epithelium (Leemans et al 2015b).…”
Section: R238mentioning
confidence: 94%
“…(2) We showed that the number of alkaline secretory vesicles in the epithelium of oviduct explants decreased significantly during sperm binding, and suggest that this generates an alkaline local microenvironment that stimulates capacitation in vitro . (3) In response to these alkaline conditions (pH 7.9), stallion spermatozoa show (a) a decreased affinity for oviduct epithelium binding and increased propensity for head-to-head agglutination (Leemans et al 2016), (b) a gradual increase in intracellular pH associated with increased protein tyrosine phosphorylation of proteins in the sperm tail (Gonzalez-Fernandez et al 2012, Aalberts et al 2013, and (c) hyperactivated motility which facilitates a limited release of spermatozoa from oviduct binding (Leemans et al 2015b). To date, however, the pH of equine oviduct fluid has not been measured during the peri-ovulatory period secretory phase of the oviduct epithelium.…”
Section: Acid-base Balance Of Oviductal Fluidmentioning
confidence: 99%